HIGH INTENSITY PHYSICAL TRAINING EXERCISE PROGRAM IN IMPROVING BREAST CANCER RELATED FATIGUE (International Journal of Physiotherapy, 2016)
Background: Breast cancer is a prevalent disease that requires intense and prolonged treatments. Because of improved detection and treatment options, the mortality rate from breast cancer has decreased, greatly increasing the number of survivors who are living with the disease and its side effects. Fatigue is one of the most common debilitating symptoms experienced by patients with cancer. It is a persistent feeling of exhaustion and decreased physical and mental capacity unrelieved by rest or sleep. The purpose of current study was to evaluate the effect of high intensity physical training exercise program in improving breast cancer related fatigue.Methods: Forty six patients suffering from breast cancer related fatigue, were randomly divided into two groups of equal number. Exercise group (E); received high intensity physical training program while Control group (C) received usual medical care and kept their habitual activity. The intensity of fatigue and quality of life score were measured at the beginning and after eight weeks of treatment.Results: Results of the study showed that there was significant reduction of fatigue after eight weeks in exercise (E) group more than control group with the percentage of improvement was 53%, 2% respectively. As regard to QOL measurements, there was significant increase of QOL score after treatment in exercise (E) group more than control group with the percentage of improvement was 43%, 3% respectively.Conclusion: High intensity physical exercise program may have beneficial effects in reduction of fatigue intensity and thereby improving quality of life in breast cancer patient.